Role of C- reactive proteins in cerebro-spinal fluid in differentiating pyogenic from nonpyogenic meningitis - Jain, Sharad; Nayak, Rashmi; Sharma, Anand (International Journal of Research in Medical Sciences, 2017)
Background:In developing countries like India meningitis is major cause of morbidity and mortility because of delay in proper diagnosis and consequently delay in proper treatment. For the appropriate treatment of meningitis, differentiation of various types of meningitis is essential. The diagnosis of meningitis in a govt. hospitals is usually made by examination of CSF, Gram staining, AFB, CSF culture and associated clinical findings. All these laboratory techniques have their limitations. So we need a diagnostic test which is rapid, reliable and cost effective. In the present study we used CRP levels in CSF sample to differentiate pyogenic from non-pyogenic meningitis and to establish a cut off level for CRP. Methods: The study is a hospital based prospective study carried out in the setting of department of pathology, microbiology, casuality and various wards of Netaji Subash Chandra Bose Medical College Jabalpur (M.P) India during November 2014 to October 2015. During study period we took samples (Blood and CSF) from 138 cases of suspected meningitis. Results: Value of CRP was 32.50645±2.032886 in PM cases, 1.543373±0.195181 in TBM cases and VM cases value were 2.420833±0.357502. Statistically significantly higher value was observed with pyogenic meningitis cases compared to TBM and VM cases. (p<0.001). At 10 U/L cut off value, sensitivity and specificity of CSF- CRP was 93.5% and 94.4% respectively. Conclusions: On the basis of present study we concluded that CRP can be used as a rapid confirmatory test since elevated CRP are highly suggestive of pyogenic meningitis.